Las voces del pueblo ecuatoriano: construcción del pueblo en el fenómeno populista de Rafael Correa - Ingrid Ríos-Rivera (Colombia Internacional)
Objective/context: To understand how Ecuadorian men and women construct the idea of “the people” through their discourses, following the populist phenomenon of Rafael Correa in Ecuador (2007–2017). Methodology: Ecuador was chosen as a case study, and through a qualitative approach, this study included 26 in-depth interviews and 4 discussion groups with people across the country. This research followed an approach based on grounded theory and discourse analysis and data processing was carried out using the Atlas.ti. Conclusions: This study provides insights into Ecuadorians’ imaginaries regarding politics and populism, and it also enabled an understanding of the collective from the individual perspective, as well as how the homogeneity of the Ecuadorian people emerges from the individuals who make it up. Originality: It addresses the narratives constructed about “the people,” focusing on those who comprise it as key actors in the Latin American populist phenomenon.